Stuart Hall's Representation: A Study of the Interpretation of Q.S. An-Nur: 26 in the Trend of Pre-Marital Studies on Social Media : Representasi Stuart Hall: Studi Penafsiran Q.S. An-Nur: 26 dalam Tren Kajian Pranikah di Media Sosial - Bramasta, Mohammad Faqih; Ihsan, Muhammad Faqih (Takwil: Journal of Quran and Hadith Studies, 2024)
The interpretation of Q.S. an-Nur: 26 has experienced a significant shift in meaning in the digital era, especially through social media. The verse, which was previously understood in the context of biological purity due to adultery, is now widely interpreted as a form of kafa'ah in religious piety, especially in the context of pre-marital studies that are rampant among the younger generation. This shift is inseparable from the high number of young people of marriageable age in Indonesia and the increasing phenomenon of hijrah which is oriented towards improving individual religious quality. This study aims to examine how Q.S. an-Nur: 26 is interpreted in social media, the factors that drive the shift in meaning, and the impact on the understanding and attitudes of netizens as consumers of da'wah content. This research uses a qualitative method with a literature study approach. Primary data is obtained from video content on TikTok accounts @untaian.ilmu and @remoteaccrusak, while secondary data comes from books of tafsir and relevant scientific literature. Data analysis was conducted through three stages: data collection, data reduction, and interpretation, using Stuart Hall's representation theory approach which includes reflective, intentional, and constructivist representations. The results showed that the interpretation of Q.S. an-Nur: 26 in the context of pre-marriage tends to emphasize the importance of equality in piety as a basis for choosing a life partner. The content invites the younger generation to “perfect themselves” before marriage as a form of spiritual self-improvement. Netizen responses show a complex dynamic, divided between positive acceptance and critical attitudes that question the relevance of the content. In general, this interpretation is considered to be able to have a positive influence in directing a religious lifestyle among young people and helping to reduce the number of early marriages and promiscuity, in line with the objectives of maqashid sharia.